2006
DOI: 10.3852/mycologia.98.6.850
|View full text |Cite
|
Sign up to set email alerts
|

Assembling the Fungal Tree of Life: constructing the Structural and Biochemical Database

Abstract: A major goal of the Assembling the Fungal Tree of Life project is to create a searchable database of selected ultrastructural and biochemical characters from published and new data for use in phylogenetic and other analyses. While developing this database such issues as evaluating specimen fixation quality in published micrographs, organizing data to accommodate characters that were dependent on location and developmental stage, and requiring accountability of data contributors were addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 46 publications
1
39
0
1
Order By: Relevance
“…These sequences matched to bacteria in the phylum Proteobacteria (65), Actinobacteria (27) and the Bacteroidetes, Firmicutes, and Planctomyces (16 combined). Based on linear regression, we found a significant positive correlation between the proportion active bacterial OTUs and the relative abundance of rpfC genes (F 1,5 =9.68, R 2 =0.59, p=0.03).…”
Section: Resuscitation Promoting Factormentioning
confidence: 95%
See 1 more Smart Citation
“…These sequences matched to bacteria in the phylum Proteobacteria (65), Actinobacteria (27) and the Bacteroidetes, Firmicutes, and Planctomyces (16 combined). Based on linear regression, we found a significant positive correlation between the proportion active bacterial OTUs and the relative abundance of rpfC genes (F 1,5 =9.68, R 2 =0.59, p=0.03).…”
Section: Resuscitation Promoting Factormentioning
confidence: 95%
“…Raw environmental sequences generated for this study can be accessed in the MG-RAST database [25] To generate phylogenies from the environmental sequences, we placed representative OTU sequences onto reference phylogenies. For the bacteria, we used an existing phylogeny from Kembel et al (2012) [26], and for the fungi, we built the reference using 952 non-redundant full-length LSU sequences from the Assembling the Fungal Tree of Life project [27] downloaded from GenBank (NCBI). Filtered fungal and bacterial OTU sequences were placed onto their respective reference trees using pplacer [28].…”
Section: Molecular Analysis Of Microbial Communitiesmentioning
confidence: 99%
“…Additional pages were contributed to the Tree of Life web project (http://www.tolweb.org/Fungi/2377) to make information on fungi more accessible to students and the general public. Two objectives of the ongoing AFTOL-2 project include increased taxon sampling of fungi for molecular data and the discovery of correlated morphological and biochemical characters (AFTOL Structural and Biochemical Database, https://aftol.umn.edu;Celio et al, 2006 ). ( Kirk et al, 2008 ) reported 97 330 species of described fungi at the " numbers of fungi " entry.…”
mentioning
confidence: 99%
“…The Assembling the Fungal Tree of Life (AFTOL) project set up yet another valuable online resource for fungi, data matrices, and phylogenetic reconstructions (29). The data elements are curated from published literature and include post-taxonomic assessments for inclusion in the AFTOL database, combining character illustrations and molecular data.…”
Section: Online Databases For Taxonomy and Identification Of Pathogenmentioning
confidence: 99%